A review of the 2023 US Draft Merger Guidelines - Rakić Ivana (Anali Pravnog Fakulteta u Beogradu)
The aim of this article is to provide a short overview of the 2023 US Draft Merger Guidelines and some interpretations of its impact on merger control practices. The US practice shows that merger control standards have been changed several times, in accordance with the need to increasingly consider economic efficiencies and the consequences of making wrong decisions, which could reduce innovation and other behaviours of undertakings that lead to an increase in economic efficiency and improve competition. Due to the fact that guidelines can influence how judges evaluate challenges to mergers, it remains to be seen how the final guidelines will enable the courts to understand and support the agencies' views on antitrust enforcement.